D-α-Tocopheryl polyethylene glycol succinate/Solutol HS 15 mixed micelles for the delivery of baohuoside I against non-small-cell lung cancer: optimization and in vitro, in vivo evaluation - Yan H (Dove Medical Press, 2016)
Hongmei Yan,1,2 Zhenhai Zhang,2 Xiaobin Jia,1,2 Jie Song1,2 1College of Pharmacy, Nanjing University of Chinese Medicine, 2Key Laboratory of New Drug Delivery System of Chinese Materia Medica, Third School of Clinical Medical of Nanjing University of Chinese Medicine, Nanjing, People’s Republic of China Abstract: Baohuoside I, extracted from the Herba epimedii, is an effective but a poorly soluble antitumor drug. To improve its solubility, formulation of baohuoside I-loaded mixed micelles with d-α-tocopheryl polyethylene glycol succinate and Solutol HS 15 (BTSM) has been developed in this study. We performed a systematic comparative evaluation of the antiproliferative effect, cellular uptake, antitumor efficacy, and in vivo tumor targeting of these micelles using non-small-cell lung cancer (NSCLC) A549 cells. Results showed that the obtained micelles have a mean particle size of ~62.54 nm, and the size of micelles was narrowly distributed. With the improved cellular uptake, BTSM displayed a more potent antiproliferative action on A549 cell lines than baohuoside I; half-maximal inhibitory concentration was 7.83 vs 20.37 µg/mL, respectively. The antitumor efficacy test in nude mice showed that BTSM exhibited significantly higher antitumor activity against NSCLC with lesser toxic effects on normal tissues. The imaging study for in vivo targeting demonstrated that the mixed micelles formulation achieved effective and targeted drug delivery. Therefore, BTSM might be a potential antitumor formulation. Keywords: baohuoside I-loaded mixed micelles, TPGS, Solutol HS 15, antitumor